Interaction of Glycemic Control and Statin Use on Diabetes-Tuberculosis Treatment Outcome: A Nested Case-Control Study - Xiangrui Meng; Huiqiu Zheng; Jian Du; Xuemei Wang; Yanling Wang; Jing Hu; Jing Zhao; Qianqian Du; Yulong Gao (Canadian Journal of Infectious Diseases and Medical Microbiology)
This study aims to explore the interaction of glycemic control and statin use on the treatment outcomes of pulmonary tuberculosis-diabetes comorbidity (PTB-DM) patients. A nested case-control study was conducted in a tuberculosis patients’ cohort. We defined cases as patients who experienced unfavorable outcomes. Glycemic control was estimated at the baseline. Statin use was obtained from medical records. The multivariate logistic regression models were developed, and the interaction table invented by Andersson was adopted to analyze the interaction of glycemic control and statin use on treatment outcomes. A total of 2,047 patients were included in this study. There was a significant interaction between glycemic control and statin use on the treatment outcomes. Patients with good glycemic control and no statin use (OR = 0.464, 95% CI: 0.360–0.623) had a lower risk of unfavorable outcomes than those with poor glycemic control and statin use (OR = 0.604, 95% CI: 0.401–0.734). Patients with good glycemic control and statin use had the lowest risk of unfavorable outcomes (OR = 0.394, 95% CI: 0.264–0.521). Glycemic control in diabetes-tuberculosis treatment should be paid considerable attention. Patients can benefit from statin use even if they have poor glycemic control. Patients with good glycemic control and statin use can have the best outcomes.